Scorpion Venom Heat-Resistant Peptide Attenuates Microglia Activation and Neuroinflammation - Wu, Xue-Fei; Li, Chun; Yang, Guang; Wang, Ying-Zi; Peng, Yan; Zhu, Dan-Dan; Sui, Ao-Ran; Wu, Qiong; Li, Qi-Fa; Wang, Bin; Li, Na; Zhang, Yue; et al. (Frontiers in Pharmacology, 2021)
Background Intervention of neuroinflammation in central nervous system (CNS) represents a potential therapeutic strategy for a host of brain disorders. The scorpion Buthus martensii Karsch (BmK) and its venom have long been used in the Orient to treat inflammation-related diseases such as rhumatoid arthritis and chronic pain. Scorpion venom heat-resistant peptide (SVHRP), a component from BmK venom, has been shown to reduce seizure susceptibility in a rat epileptic model and protect against cerebral ischemia-reperfusion injury. As neuroinflammation has been implicated in chronic neuronal hyperexcitability, epileptogenesis and cerebral ischemia-reperfusion injury, the present study aimed to investigate whether SVHRP has anti-inflammatory property in brain. Methods An animal model of neuroinflammation induced by lipopolysacchride (LPS) injection was employed to investigate the effect of SVHRP (125 µg/kg, intraperitoneal injection) on inflammagen-induced expression of pro-inflammatory factors and microglia activation. The effect of SVHRP (2-20 μg/ml) on neuroinflammation was further investigated in primary brain cell cultures containing microglia as well as the immortalized BV2 microglia culture stimulated with LPS. Real-time quantitative PCR were used to measure mRNA levels of inducible nitric oxide synthase (iNOS), tumor necrosis factor-α (TNF-α), interleukin (IL)-1 and IL-6 in hippocampus of animals. Protein levels of TNF-α, iNOS, P65 subunit of nuclear factor-κB (NF-κB) and mitogen-activated protein kinases (MAPKs) were examined by ELISA or western blot. Microglia morphology in animal hippocampus or cell cultures and cellular distribution of p65 were shown by immunostaining. Results Morphological study demonstrated that activation of microglia, the main component that mediates the neuroinflammatory process, was inhibited by SVHRP in both LPS mouse and cellular model. Our results also showed dramatic increases in the expression of iNOS and TNF-α in hippocampus of LPS-injected mice, which was significantly attenuated by SVHRP treatment. In vitro results showed that SVHRP attenuated LPS-elicited expression of iNOS and TNF-α in different cultures without cell toxicity, which might be attributed to suppression of NF-κB and MAPK pathways by SVHRP. Conclusions Our study demonstrates that SVHRP is able to inhibit neuroinflammation and microglia activation, which may underlie the therapeutic effects of BmK-derived materials, suggesting that BmK venom could be a potential source for CNS drug development.